Dysfunctional coping is related to impaired skin‐related quality of life and psychological distress in patients with neurofibromatosis type 1 with major skin involvement. (1st June 2020) - Bottesi, G.; Spoto, A.; Trevisson, E.; Zuccarello, D.; Vidotto, G.; Cassina, M.; Clementi, M.
Summary: Background: Low skin‐related quality of life (QoL) is usually associated with low levels of self‐confidence and self‐esteem and with high levels of anxiety and depression symptoms. The way patients cope with a physical disease impacts significantly on their psychosocial adjustment to the disorder and on their emotional functioning. Objectives: To explore how coping strategies, skin‐related QoL, psychological distress and self‐esteem interact in a sample of individuals with neurofibromatosis type 1 (NF1). Methods: Seventy‐two adult patients with NF1 completed the following questionnaires: Coping Orientation to Problem Experiences (COPE), Skindex‐29, Padua Skin‐Related QoL questionnaire (PSRQ), State–Trait Anxiety Inventory‐X2 form (STAI‐X2), Depression Questionnaire (DQ) and Rosenberg Self‐Esteem Scale (RSES). The k‐modes algorithm was used to identify clusters of patients based on four variables: sex, NF1 severity, number and distribution of cutaneous neurofibromas. Individuals in different clusters were compared with regard to their scores; correlations between scores were analysed within each cluster. Results: Two main clusters were identified: individuals in Cluster 1 had a larger number and more widespread distribution of neurofibromas compared with Cluster 2. Patients in Cluster 1 scored higher only on several PSRQ and Skindex‐29 scales. Among patients in Cluster 1, the COPE 'avoidance strategies' scale was significantly correlated with the PSRQ 'physical distress and impairments' scale, the Skindex‐29 'physical symptoms' and 'functioning' scales, the STAI‐X2, the DQ and the RSES. Conclusions: Patients with major skin involvement have reduced skin‐related QoL. Among them, current findings tentatively suggest that the higher the use of dysfunctional coping, the more impaired are QoL, psychological distress and self‐esteem. What's already known about this topic? Neurofibromatosis type 1 (NF1) can affect the quality of life (QoL) in adolescent and adult patients. Low skin‐related QoL is usually associated with low levels of self‐confidence and self‐esteem and with high levels of anxiety and depression symptoms. Questionnaires evaluating skin‐related QoL, anxiety, depression, self‐esteem and coping are available. What does this study add? Patients with a large number and a widespread distribution of cutaneous neurofibromas have reduced skin‐related QoL compared with patients with minor skin involvement. The newly developed Padua Skin‐Related QoL questionnaire allows the simultaneous evaluation of discomfort and comfort skin‐related QoL dimensions in patients with NF1. Among patients with major skin involvement, the higher the use of dysfunctional coping, the more impaired are skin‐related QoL, psychological distress and self‐esteem. Our data suggest that patients with NF1 with major skin involvement who endorse dysfunctional beliefs about their own coping abilities might benefit from psychological counselling and coping skills treatments aiming to both improve perceived self‐efficacy and learn more adaptive coping strategies.